Research on coordinated control of renewable-energy-based Heat-Power station system. (15th October 2022) - Lei, Xuanang; Lin, Yujun; Yang, Qiufan; Zhou, Jianyu; Chen, Xia; Wen, Jinyu
Highlights: A novel CHP system adopting only renewable energy as energy input is constructed. A coordinated control strategy for renewable-energy-based heat-power station (REHPS) is proposed. Dynamic characteristics of the controller are analyzed for the parameter design. REHPS under the proposed control strategy can meet the multi-energy demand of users. Simulation and experimental results verify the effectiveness of the proposed control strategy. Abstract: The traditional combined heat and power (CHP) units have drawbacks such as a lack of flexibility in control and environmental pollution. Renewable-energy-based heat-power station (REHPS) system utilizes renewable energy to produce electricity and heat with the advantages of cleanness, high efficiency, and flexibility. The previous studies on CHP mainly focus on optimal scheduling, and its operation control is seldom considered. This paper proposes a coordinated control strategy of REHPS to ensure stable and reliable operation. Firstly, the dynamical model of REHPS is established and the operational principle and dynamic characteristics are analyzed. Secondly, a double-layer coordinated control strategy is proposed for smoothing power fluctuation in the lower layer and meeting the demand of thermal load in the upper layer. The dynamic characteristics of the controller are analyzed for the parameter design to match the dynamic response time of the energy storages. Finally, simulations and experimental studies are conducted to demonstrate the effectiveness of the proposed coordinated control in the REHPS system under different scenarios. The results show that the system operates stably and the indoor temperature is maintained at around 25 °C. Compared with the previous study, the maximum voltage overshoot is decreased by 11.2% under wind speed fluctuations and the temperature difference is controlled within about 0.5 °C under thermal load variation under the proposed control. The research on REHPS control provides a new solution to meet the multi-energy demands of users.